Studi Kasus Terhadap Alat Penukar Kalor 127-C PUSRI IV Berbasis Simulasi Program Heat Transfer Research Inc. (HTRI) Dengan Variabel Jumlah Plug dan Material Tube - Nucke Aurelia; Lia Cundari; Winandyo Mangkoto (LPPM, 2022)
Heat exchanger (HE) is used as a medium for heat exchange between fluids. One of the most critical HE at PUSRI, is the 127-C (Ammonia Refrigerant Condenser) in the PUSRI-IV ammonia unit which is supported by 2 identical HEs, namely 127-CA and 127-CB. This HE serves to condense ammonia gas into liquid ammonia. After evaluating the performance of this HE, there was an average decrease of 31.46%. Therefore, it is necessary to optimize this HE, one of which is through research using the HTRI (Heat Transfer Research Inc.) simulator to see the effect of the number of plugs and tube material replacement. The variable number of plugs used are 17, 250, 500, 750 and 1000 for the 127-CA and 21, 250, 500, 750 and 1000 for the 127-CB. As for the tube material variables, namely Carbon Steel (CS), 304- Stainless Steel (304-SS), and 316- Stainless Steel (316-SS). After simulation and analysis were carried out by considering the factors of heat transfer performance, corrosion resistance and cost-benefit, it was concluded that re-tubing with 304-SS material was the most appropriate choice. The maximum number of plugs for CS material is 1000 pieces while for 304-SS and 316-SS materials it is 750 pieces. Heat exchanger (HE) is used as a medium for heat exchange between fluids. One of the most critical HE at PUSRI, is the 127-C (Ammonia Refrigerant Condenser) in the PUSRI-IV ammonia unit which is supported by 2 identical HEs, namely 127-CA and 127-CB. This HE serves to condense ammonia gas into liquid ammonia. After evaluating the performance of this HE, there was an average decrease of 31.46%. Therefore, it is necessary to optimize this HE, one of which is through research using the HTRI (Heat Transfer Research Inc.) simulator to see the effect of the number of plugs and tube material replacement. The variable number of plugs used are 17, 250, 500, 750 and 1000 for the 127-CA and 21, 250, 500, 750 and 1000 for the 127-CB. As for the tube material variables, namely Carbon Steel (CS), 304- Stainless Steel (304-SS), and 316- Stainless Steel (316-SS). After simulation and analysis were carried out by considering the factors of heat transfer performance, corrosion resistance and cost-benefit, it was concluded that re-tubing with 304-SS material was the most appropriate choice. The maximum number of plugs for CS material is 1000 pieces while for 304-SS and 316-SS materials it is 750 pieces.